Chemical Degradation of Epoxy-Polyamide Primer by Electrochemical Impedance Spectroscopy. (9th July 2012) - Duraisamy, Ramesh; Pownsamy, Kannan; Asgedom, Ghebray
Abstract : The degradation of organic-inorganic hybrid materials based on epoxy resin was characterized electrochemically in aggressive chemical electrolyte. In the present study, the hybrid material as primer was prepared from epoxy resin pigmented by zinc phosphate cured with polyamide (EPZ). The hybrid material was coated on mild steel substrate, and the corrosion behavior was studied by electrode-potential time measurements and mainly by electrochemical impedance spectroscopy (EIS) in 5% NaCl solution. The impedance parameters, namely, coating capacitance (C c ), pore resistance (R po ), charge transfer resistance (R t ), double layer capacitance (C d1 ), and break point frequency (f b ), corresponding to 45° phase angle as a function of time of exposure were estimated. The observed impedance behavior were compared with the established equivalent electrical circuit represents the coated metal/electrolyte interface. Changes in the values of the circuit components given the information on the stages of degradation and physical phenomenon occurring throughout the degradation of primer coating were also been predicted. In addition, information related to the porous nature of the primer, limited passivation effect, and delamination of coating with longer exposure that resulted in the diffusion controlled corrosion of metal are also recognized. Thus, results indicate that the EPZ coating had good corrosion resistance. This could be a nonpolluting alternative to the traditional chromate like environmentally harmful coatings.